Photodynamic Therapy Efficacy Enhanced by Dynamics: The Role of Charge Transfer and Photostability in the Selection of Photosensitizers. Issue 18 (18th March 2014) - Arnaut, Luis G.; Pereira, Mariette M.; Dąbrowski, Janusz M.; Silva, Elsa F. F.; Schaberle, Fábio A.; Abreu, Artur R.; Rocha, Luís B.; Barsan, Madalina M.; Urbańska, Krystyna; Stochel, Grażyna; Brett, Christopher M. A.
Abstract Progress in the photodynamic therapy (PDT) of cancer should benefit from a rationale to predict the most efficient of a series of photosensitizers that strongly absorb light in the phototherapeutic window (650–800 nm) and efficiently generate reactive oxygen species (ROS=singlet oxygen and oxygen‐centered radicals). We show that the ratios between the triplet photosensitizer–O2 interaction rate constant (kD) and the photosensitizer decomposition rate constant (kd), kD/kd, determine the relative photodynamic activities of photosensitizers against various cancer cells. The same efficacy trend is observed in vivo with DBA/2 mice bearing S91 melanoma tumors. The PDT efficacy intimately depends on the dynamics of photosensitizer–oxygen interactions: charge transfer to molecular oxygen with generation of both singlet oxygen and superoxide ion (high kD) must be tempered by photostability (low kd). These properties depend on the oxidation potential of the photosensitizer and are suitably combined in a new fluorinated sulfonamide bacteriochlorin, motivated by the rationale.